Games for teaching english as contextual communication in elemantary school - Aucancela Chitacapa, Clara; Jiménez Pintado, Jenny
Massive failures, both on course - disapproval and on learning effectiveness, have led us to undertake this challenging duty of changing elementary School English teachers´ philosophy with respect to their way to teach English through the use of English Learning games. "Games for Teaching English as Contextual Communication in Elementary School" is a research project which provides us with new and modern theories aimed to give the students a new perspective addressed to socialize, give confidence, certainly and get them able to communicate through the use of English Learning games. This way we put into practice some selected learning games in "San Diego de Alcala" and "San Francisco de Asis" schools. From this experimentation we assert that games are essential tools in English classes because children enjoy playing them. Besides, games add variation to a lesson and increase students´ motivation. When we experimmented games, students were willing and eager to participate, which resulted in a significant improvement of their performance. At the end of the game they wanted to keep on playing and showed as enthusiastic as at the beginning.Consequently, as a final conclusion we would like to advice every English teacher that he/she use learning games as often as possible when it comes to arise kids` interest, get their attention, and reach a high quality performance